Peningkatan Keterampilan Bisnis Pelaku UMKM Handycraft melalui Pelatihan Digital Marketing dan Keuangan - Fatoni, Fandi; Kistyanto, Anang; Hatono, Ulil; Paramita, R. A Sista; Ramadhani, Bima Yatna Anugerah (Jurnal Abdi Masyarakat (JAM), 2024)
This Community Service activity targets productive community groups, namely handicraft MSMEs, Kapas District, Bojonegoro Regency. Based on the results of problem identification, it is known that the priority problems are 1) integrated digital marketing and 2) financial literacy. The training implementation method uses tutorial and lecture techniques. The target to be achieved from the implementation of this service is to gain knowledge and understanding for partners regarding digital marketing and financial literacy for handicraft MSMEs, Kapas District, Bojonegoro Regency. The results of the training evaluation in Klampok Village, Kapas Bojonegoro District for UKM Handycraft partners show that partners need support to improve their marketing through the use and management of digital marketing as well as changing the mindset that partners need to carry out good business financial management and family financial management so that family prosperity can be achieved.